Budaya Organisasi Terhadap Kinerja Karyawan Melalui Komitmen - Yuyuk Liana (Jurnal Manajerial, 2020)
Background - Human resources are an important factor in an organization and must be of good quality, that is to have a competent spirit and also perform well. The existing commitment in employees towards the organization is an important instrument for improving employee performance. Organizational culture is a need to be developed in an organization with the aim to be able to overcome all problems that arise. Organizational culture can be said to be good when it can be proven by looking at employee turnover Aim - This study aims to determine the direct and indirect effects of organizational culture variables, organizational commitment and employee performance. Design / methodology / approach – This research belongs to exploratory field research to explain the relationship between organizational culture and employee performance. The number of respondents involved was 100 respondents, all of whom were employees at the One Stop Integrated Capital and Service Office in East Kalimantan. Research instruments using questionnaires, research analysis using path analysis. Finding – The results prove all paths in this path analysis are significant. Employees in the organization need an understanding of the culture in the organization so that performance increases while there is also an element of commitment that is a variable between the organizational culture and employee performance. Research Implication – In this study has the implication of providing direction for organizational behavior research by taking into account organizational factors and other individual factors that can improve employee performance in the organization. besides that, in subsequent studies can add the variable job satisfaction, motivation. Limitation – The limitation that can affect the results of this study is to use a questionnaire so that the possibility of researchers less anticipating respondents who just answered